(untitled) (Research, Society and Development, 2021)
Report the case of a 51-year-old man, who evolved insidiously with tetraparesis after firearm cervical injury 19 years ago, presenting with polyarthralgia, headache, abdominal pain, constipation, polyneuropathy and anemia. Given the diagnostic hypothesis of lead poisoning due to the high serum and urinary levels of lead, surgical removal of projectile in the cervical region was chosen, obtaining clinical improvement. After 5 months, he was readmitted with a relapse of the abdominal and anemic symptoms. Abdomen tomography revealed a possible projectile fragment on right rectus abdominis muscle. On hospitalization, he presented fever, polyarthralgia with fist monoarthritis and phlogistic signs on left bulging elbow, which was punctured. Literature review shows increased reabsorption of uric acid on lead poisoned patients added to the patient antecedent of Gout so we decide to treat the patient with anti-inflammatory drugs and prednisone, with clinical improvement. The study of liquid revealed calcium pyrophosphate crystals, contrasting gouty arthritis diagnosis. Patient underwent surgery to remove the projectile in the rectus abdominis muscle, we decided not to prescribe chelating, due to the serum lead level below 50 mcg/dl and clinical patient improvement, who was discharged a few days later. We report this case due to the rarity of this association. We hope to raise a possible association of these pathologies with an unknown pathophysiological mechanism not yet described in medical clinic books and with only one case published in world literature.